2005
DOI: 10.1111/j.1349-7006.2005.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of Dicer associated with poor prognosis in lung cancer patients

Abstract: Emerging evidence suggests that microRNA, which are wellconserved, abundant and small regulatory RNA, may be involved in the pathogenesis of human cancers. We recently reported that expression of let-7 was frequently reduced in lung cancers, and that reduced let-7 expression was significantly associated with shorter patient survival. Two members of the double-stranded RNA-specific endonuclease family, Dicer and Drosha, convert precursor forms of microRNA into their mature forms using a stepwise process. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
414
1
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(449 citation statements)
references
References 28 publications
26
414
1
5
Order By: Relevance
“…Micheal et al reported that mirs-143 and -145 consistently display reduced steady-state levels of the mature miRNA at the adenomatous and cancer stages of colorectal cancers and that in cancer cells decreased levels of mature miRNAs was due to reduced Dicer-processing activity. In our study, since the introduction of mir-143 or -145 precursors into the DLD-1 and SW480 cells caused growth inhibition, the activity and expression of Dicer and RNA-induced silencing complex (RISC) proteins which exert the enzymatic modification of precursor miRNAs seemed to be intact (16)(17)(18). Therefore, we propose that the cause of inadequate expression of mirs-143 and -145 was due to the perturbation of transcription and/or the enzymatic process of the transition from primary miRNAs to precursor ones including Drosha and DGCR8, events that occur in the nucleus (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Micheal et al reported that mirs-143 and -145 consistently display reduced steady-state levels of the mature miRNA at the adenomatous and cancer stages of colorectal cancers and that in cancer cells decreased levels of mature miRNAs was due to reduced Dicer-processing activity. In our study, since the introduction of mir-143 or -145 precursors into the DLD-1 and SW480 cells caused growth inhibition, the activity and expression of Dicer and RNA-induced silencing complex (RISC) proteins which exert the enzymatic modification of precursor miRNAs seemed to be intact (16)(17)(18). Therefore, we propose that the cause of inadequate expression of mirs-143 and -145 was due to the perturbation of transcription and/or the enzymatic process of the transition from primary miRNAs to precursor ones including Drosha and DGCR8, events that occur in the nucleus (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Reduced expression of Dicer also has been shown to be involved in lung cancer and is associated with a reduced life span of cancer patients. 13 While the majority of miRNA genes seem to be downregulated in cancer (see below), some miRNAs tend to be upregulated. Human B cell lymphomas, for example, show elevated levels of miR-155, which is derived from the nonprotein-coding transcript of the proto-oncogene BIC.…”
Section: The Role Of Mirnas In Human Tumorigenesismentioning
confidence: 99%
“…They have been found to have roles in cell growth, differentiation, apoptosis and tumourigenesis. [7][8][9][10][11][12][13][14] Furthermore, unique microRNA expression profiles have been able to classify various cancers. Recently, microRNAs were implicated in the development of ovarian cancer: 39 microRNAs are differentially regulated between tumour and normal ovarian tissue.…”
mentioning
confidence: 99%